Hypomethylation of Notch1 DNA is associated with the occurrence of uveitis. (1st July 2020) - Wei, H; Yin, X; Tang, H; Gao, Y; Liu, B; Wu, Q; Tian, Q; Hao, Y; Bi, H; Guo, D
Summary: Uveitis is a serious intra-ocular inflammatory disease that can lead to visual impairment even blindness worldwide. Notch signaling can regulate the differentiation of naive CD4 + T cells, influencing the development of uveitis. DNA methylation is closely related to the autoimmune diseases. In this study, we measured the Notch1 DNA methylation level, determined the Notch1 and related DNA methylases mRNA expression and evaluated the ratio of T helper type 17 regulatory T cell (Th17/Treg ) in peripheral blood mononuclear cells (PBMCs) from uveitis patients and normal control subjects; we also tested the levels of relevant inflammatory cytokines in serum from the participants. Results indicated that compared with those in normal control individuals, the expression of ten–eleven translocation 2 (TET2) and Notch1 mRNA is elevated in uveitis patients, whereas the methylation level in Notch1 DNA promotor region [−842 ~ −646 base pairs (bp)] is down-regulated, and is unrelated to anatomical location. Moreover, the Th17/Treg ratio is up-regulated in PBMCs from uveitis patients, accompanied by the elevated levels of proinflammatory cytokines [e.g. interleukin (IL)-2, IL-6, IL-17 and interferon (IFN)-γ] in serum from uveitis patients. These findings suggest that the over-expression of TET2 DNA demethylase may lead to hypomethylation of Notch1, activate the Notch1 signaling, induce naive CD4 + T cells to differentiate the Th17 subset and thus disturb the balance of the Th17/Treg ratio in uveitis patients. Overall, hypomethylation of Notch1 DNA is closely associated with the occurrence of uveitis. Our study preliminarily reveals the underlying mechanism for the occurrence of uveitis related to the hypomethylation of Notch1 DNA, providing a novel therapeutic strategy against uveitis in clinical practice. Graphical Abstract: